2022
DOI: 10.1186/s12887-022-03254-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with cochlear implants in Kazakhstan

Abstract: Background Although cochlear implantation (CI) has been performed in Kazakhstan since 2007 little is known about quality of life of patients after CI. The aim of this study was to assess the health-related quality of life (HRQoL) of Kazakhstani children after CI. Methods Altogether, 53 families with a child using a cochlear implant for at least 1 year participated in the study between July 20, 2019 and February 20, 2020 at the Audiological Сenter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Table 10 displays pairwise mean differences between samples. Byckova et al (2018) , Huttunen et al (2009) , Kumar et al (2015) , and Zhumabayev et al (2022) tended to support more positive QoL on this subscale compared to the other samples. Also, Brewis et al (2020) reported significantly higher values than Archbold et al (2008) , Fortunato-Tavares et al (2012) , de Almeida et al (2015 ; <24mo and >24mo), Molla et al (2019) , and Shahmahmood et al (2020) .…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Table 10 displays pairwise mean differences between samples. Byckova et al (2018) , Huttunen et al (2009) , Kumar et al (2015) , and Zhumabayev et al (2022) tended to support more positive QoL on this subscale compared to the other samples. Also, Brewis et al (2020) reported significantly higher values than Archbold et al (2008) , Fortunato-Tavares et al (2012) , de Almeida et al (2015 ; <24mo and >24mo), Molla et al (2019) , and Shahmahmood et al (2020) .…”
Section: Resultsmentioning
confidence: 75%
“…Although education traditionally tends to be ranked relatively low among QoL indicators ( Hyde et al, 2010 ; Zhao et al, 2018 ; Bhamjee et al, 2019 ), global parent proxy reports using the CCIPP ranged considerably from ranking education and academics as the second lowest level of QoL ( Kumar et al, 2015 ; Zhumabayev et al, 2022 ) to the second highest level of QoL ( Molla et al, 2019 ; Anne et al, 2021 ) across the subscales. Differences in appraising cochlear implantation relative to academics could indicate country-specific differences in the emphasis on academics in Bangladesh ( Molla et al, 2019 ), Kazakhstan ( Zhumabayev et al, 2022 ), and the United States ( Kumar et al, 2015 ; Anne et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also found that HRQOL was more limited in children with bilateral hearing loss than those with unilateral hearing loss. It has been stressed in other studies that children having cochlear implants were found to have similar HRQOL to healthy children [51][52][53][54][55]. Changes in hearing threshold and tinnitus severity after stapes surgery have also been found to be important to quality of life in adult patients [56].…”
Section: Discussionmentioning
confidence: 96%
“…then the local symptoms reported include: changes in breathing pattern to mouth breathing (adenoid faces/long face syndrome), malocclusion, altered voice timbre, night snoring, and night apnea. Furthermore, an enlarged adenoid may impair the patency of the Eustachian tube which, inter alia, can lead to exudative otitis media, that may lead to hearing loss [49][50][51][52][53][54][55]. Symptoms of tonsil hypertrophy are snoring, obstructive sleep apnea syndrome, speech disorders such as slurred speech, and dysphagia (especially with solid foods) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]51,55].…”
Section: Discussionmentioning
confidence: 99%